Potret Implementasi Capacity Building dalam Layanan Repositori Institusi Perpustakaan Perguruan Tinggi: Studi Kasus pada Brawijaya Knowledge Garden (BKG) - Mochammad Rozikin; Mukhlis (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
The presence of institutional repositories is a relatively new service method in dissemination practices as well as ideal for supporting the visibility of universities. This success is inseparable from the implementation of capacity building, which is interesting to study. This paper uses a descriptive-qualitative perspective. The method used is a case study to examine aspects of capacity building in the Brawijaya Knowledge Garden (BKG) with three main aspects, namely effectiveness (effectively), efficiency (efficiently), and sustainability (sustainable). The aim is to reveal the effect of capacity development on the institutional repository system and to find the patterning of synergistic aspects between capacity development and institutional repository governance at Brawijaya Knowledge Garden (BKG).There are three main findings in this paper. The effectiveness aspect describes the repository access model that can be done online; in addition, the repository is also multi-platform and can be accessed using a variety of operating systems, such as Windows, Lynx, and Mac; second, the efficiency aspect is related to the maximization of use and dissemination by users. The efficiency aspect of the repository can be seen in the content search process, such as the use of a number of search options that can be selected; third, the sustainable aspect includes the management of scientific work carried out based on the increasing number of works deposited each time. Finally, the integration between capacity building components and Brawijaya Knowledge Garden (BKG) services forms a synergistic pillar and forms an integrative cycle between capacity building and institutional repositories in university libraries that is interesting to continue to be studied from time to time.